Integration of chemosensory pathways in the Drosophila second-order olfactory centers. - Tanaka, N.K.; Awasaki, T.; Shimada, T.; Ito, K. (Current Biology, 2004)
Behavioral responses to odorants require neurons of the higher olfactory centers to integrate signals detected by different chemosensory neurons. Recent studies revealed stereotypic arborizations of second-order olfactory neurons from the primary olfactory center to the secondary centers, but how third-order neurons read this odor map remained unknown.Using the Drosophila brain as a model system, we analyzed the connectivity patterns between second-order and third-order olfactory neurons. We first isolated three common projection zones in the two secondary centers, the mushroom body (MB) and the lateral horn (LH). Each zone receives converged information via second-order neurons from particular subgroups of antennal-lobe glomeruli. In the MB, third-order neurons extend their dendrites across various combinations of these zones, and axons of this heterogeneous population of neurons converge in the output region of the MB. In contrast, arborizations of the third-order neurons in the LH are constrained within a zone. Moreover, different zones of the LH are linked with different brain areas and form preferential associations between distinct subsets of antennal-lobe glomeruli and higher brain regions.MB is known to be an indispensable site for olfactory learning and memory, whereas LH function is reported to be sufficient for mediating direct nonassociative responses to odors. The structural organization of second-order and third-order neurons suggests that MB is capable of integrating a wide range of odorant information across glomeruli, whereas relatively little integration between different subsets of the olfactory signal repertoire is likely to occur in the LH.